Solve for m
\left\{\begin{matrix}\\m=0\text{, }&\text{unconditionally}\\m\in \mathrm{R}\text{, }&\left(s=\frac{\sqrt{691186729}t-15277t}{14000}\text{ or }s=\frac{-\sqrt{691186729}t-15277t}{14000}\right)\text{ and }t\neq 0\end{matrix}\right.
Solve for s
\left\{\begin{matrix}\\s\neq 0\text{, }&\text{unconditionally}\\s=\frac{\left(\sqrt{691186729}-15277\right)t}{14000}\text{; }s=-\frac{\left(\sqrt{691186729}+15277\right)t}{14000}\text{, }&t\neq 0\end{matrix}\right.
Share
Copied to clipboard
0=2s^{2}\left(2.1m+\frac{4.5831m}{s}t\right)-\frac{1}{2}\times 2\times 9.81mt^{2}
Multiply both sides of the equation by 2s^{2}, the least common multiple of s,2,s^{2}.
0=4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t-\frac{1}{2}\times 2\times 9.81mt^{2}
Use the distributive property to multiply 2s^{2} by 2.1m+\frac{4.5831m}{s}t.
0=4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t-9.81mt^{2}
Multiply \frac{1}{2} and 2 to get 1.
4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t-9.81mt^{2}=0
Swap sides so that all variable terms are on the left hand side.
s\left(4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t\right)-9.81mt^{2}s=0
Multiply both sides of the equation by s.
s\left(4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t\right)s-9.81mt^{2}ss=0
Multiply both sides of the equation by s.
s^{2}\left(4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t\right)-9.81mt^{2}ss=0
Multiply s and s to get s^{2}.
4.2ms^{4}+2\times \frac{4.5831m}{s}ts^{4}-9.81mt^{2}ss=0
Use the distributive property to multiply s^{2} by 4.2s^{2}m+2s^{2}\times \frac{4.5831m}{s}t.
4.2ms^{4}+2\times \frac{4.5831m}{s}ts^{4}-9.81mt^{2}s^{2}=0
Multiply s and s to get s^{2}.
4.2ms^{4}s+2\times 4.5831mts^{4}-9.81mt^{2}s^{2}s=0
Multiply both sides of the equation by s.
4.2mss^{4}-9.81mss^{2}t^{2}+2\times 4.5831mts^{4}=0
Reorder the terms.
4.2ms^{5}-9.81mss^{2}t^{2}+2\times 4.5831mts^{4}=0
To multiply powers of the same base, add their exponents. Add 1 and 4 to get 5.
4.2ms^{5}-9.81ms^{3}t^{2}+2\times 4.5831mts^{4}=0
To multiply powers of the same base, add their exponents. Add 1 and 2 to get 3.
4.2ms^{5}-9.81ms^{3}t^{2}+9.1662mts^{4}=0
Multiply 2 and 4.5831 to get 9.1662.
\left(4.2s^{5}-9.81s^{3}t^{2}+9.1662ts^{4}\right)m=0
Combine all terms containing m.
\left(-\frac{981t^{2}s^{3}}{100}+\frac{45831ts^{4}}{5000}+\frac{21s^{5}}{5}\right)m=0
The equation is in standard form.
m=0
Divide 0 by 4.2s^{5}-9.81s^{3}t^{2}+9.1662ts^{4}.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}